Human aminolevulinate synthase structure reveals a eukaryotic-specific autoinhibitory loop regulating substrate binding and product release - Henry J. Bailey (Nature Portfolio, 2020)
Mutation of the C-terminal extension of 5′-aminolevulinate synthase 2 (ALAS2) is the molecular cause for X-linked protoporphyria, but the underlying mechanism is unclear. Based on crystal structures and MD simulations of ALAS2, the authors here show how the C-terminal extension regulates ALAS2 activity.